2005
DOI: 10.1038/sj.jp.7211407
|View full text |Cite
|
Sign up to set email alerts
|

Discharge outcomes of extremely low birth weight infants with spontaneous intestinal perforations

Abstract: Objective: To examine discharge outcomes of extremely low birth weight infants (ELBW) with spontaneous intestinal perforation (SIP).Study design: A single-center retrospective cohort study of all ELBW infants admitted to the University of Virginia neonatal intensive care unit between July 1996 and June 2004. Results:We found 35 patients with SIP (incidence 8.4%). The median gestational age was 25 weeks, median birth weight was 722 g, and 71% of the infants were male. Most infants (n ¼ 28) with SIP were diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…34 The clinical findings at presentation were similar in our group to those reported previously. [2][3][4]6,8,14 The recent prospective cohort study by the National Institute of Child Health and Human Development Neonatal Research Network on postoperative outcomes of ELBW with NEC or isolated intestinal perforation 35 has reported that the variables that most accurately predict the diagnosis of SIP are the absence of pneumatosis, the presence of a gasless abdomen, and the age at surgery. There is ongoing debate as to surgical options for infants suffering from SIP.…”
Section: Discussionmentioning
confidence: 99%
“…34 The clinical findings at presentation were similar in our group to those reported previously. [2][3][4]6,8,14 The recent prospective cohort study by the National Institute of Child Health and Human Development Neonatal Research Network on postoperative outcomes of ELBW with NEC or isolated intestinal perforation 35 has reported that the variables that most accurately predict the diagnosis of SIP are the absence of pneumatosis, the presence of a gasless abdomen, and the age at surgery. There is ongoing debate as to surgical options for infants suffering from SIP.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous intestinal perforation (SIP) is a serious morbidity affecting ELBW infants, with an incidence ranging from 3-8 % ( 1, 2 ). It has been recognized as an entity distinct from necrotizing enterocolitis (NEC) ( 3-5 ) and has been proposed to occur in infants of lower birth weight and at an earlier postnatal age ( 1, 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings in our study, the occult perforations in their study also presented in their smaller, more immature patients and were noted to occur at a later time period, some even past 3 weeks. 20 In this study, ultrasound was not routinely used in all infants suspected to have SIP, only as an adjunct in those cases where it was suspected but pneumoperitoneum was not present. Also, not every patient in their study received a peritoneal tap or had surgery performed, so it is unknown if patients who did receive abdominal ultrasounds had a confirmed surgical diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Also, not every patient in their study received a peritoneal tap or had surgery performed, so it is unknown if patients who did receive abdominal ultrasounds had a confirmed surgical diagnosis. 20 This may be important because we had a small number of patients with false-positive ultrasounds in our study.…”
Section: Discussionmentioning
confidence: 98%